3D Brochosomes‐Like TiO2/WO3/BiVO4 Arrays as Photoanode for Photoelectrochemical Hydrogen Production. Issue 28 (4th June 2019) - Pan, Qin; Zhang, Haifeng; Yang, Yaping; Cheng, Chuanwei
Abstract: An ideal photoelectrochemical (PEC) anode should process effective light absorption, charge transport, and separation efficiency. Here, a novel 3D brochosomes‐like TiO2 /WO3 /BiVO4 array as an efficient photoanode by combining a colloid polystyrene sphere template and electrochemical deposition routes for PEC hydrogen generation is reported. The as‐fabricated 3D TiO2 /WO3 /BiVO4 brochosomes photoanode yields excellent PEC performance with photocurrent densities of ≈3.13 and ≈4.27 mA cm −2 with FeOOH/NiOOH catalyst, respectively, measured in 0.5m Na2 SO4 solution with 0.1m Na2 SO3 at 1.23 V versus reversible hydrogen electrode (RHE) under simulated AM1.5 light illumination, which is ≈6 times the reference sample of a planar WO3 /BiVO4 film electrode. The significantly improved performance could be benefited from the ordered hollow porous structure that provides enhanced light absorption and efficient charge transport as well as improved charge separation efficiency by WO3 /BiVO4 "host–guest" heterojunctions. Abstract : A novel 3D brochosomes‐like TiO2 /WO3 /BiVO4 array photoanode is designed, yielding a significantly improved photoelectrochemical performance.